Customer Review, Influencer Endorsement, and Purchase Intention: The Moderating Role of Brand Image - Dedi Iskamto; Khaerunnisa Fauziah Rahmalia (Shirkah: Journal of Economics and Business, 2023)
Investigating the increasing prominence of influencer endorsements and customer reviews represents a crucial and compelling area of research. Influencer endorsement and customer reviews can influence a customer's purchasing interest in a product. This study aims to examine the influence of consumer reviews and influencer endorsement on the purchase intention of Avoskin products, taking into account the role of brand image as a moderator. The study involved 385 skincare enthusiast respondents in Indonesia and used a questionnaire as the data collection instrument. Employing multiple linear regression, the results showed that consumer reviews and influencer endorsement have a positive and significant effect on the purchase intention of Avoskin products. The brand image also plays an important role as a moderator in the relationship between consumer reviews, influencer endorsement, and purchase intention. These findings provide advice to Avoskin to improve product and service quality to improve brand image, and to increase consumer purchase intention through influencer support and customer reviews.